Habitual caffeine consumption moderates the antidepressant effect of dorsomedial intermittent theta-burst transcranial magnetic stimulation. (December 2021) - Frick, Andreas; Persson, Jonas; Bodén, Robert
Background: Potentiating current antidepressant treatment is much needed. Based on animal studies, caffeine may augment the effects of currently available antidepressants. Objective: Here, we tested whether habitual caffeine consumption moderates the antidepressant effects of repetitive transcranial magnetic stimulation (rTMS) using intermittent theta-burst stimulation (iTBS). Methods: Forty patients with current depressive episodes were randomized to active iTBS ( n  = 19) or sham treatment ( n  = 21; shielded side of the coil and weak transcutaneous electrical stimulation) delivered two times per day for 10–15 weekdays. Neuronavigated stimulation was applied to the dorsomedial prefrontal cortex. Symptom improvement was measured using change in self-reported Montgomery-Åsberg Depression Rating Scale (MADRS) scores. Pretreatment habitual caffeine consumption was quantified using self-reports of number of cups of coffee and energy drinks consumed the 2 days before the treatment starts. Results: Habitual caffeine consumption was associated with symptom improvement following active iTBS ( r  = 0.51, 95% confidence interval (CI): 0.08–0.78, p  = 0.025) but not following sham treatment ( r  = −0.02, 95% CI: −0.45 to 0.42, p  = 0.938). A multiple regression analysis corroborated the findings by showing a significant caffeine consumption × treatment group interaction (β = 0.62, p  = 0.043), but no main effects of treatment group (β = 0.22, p  = 0.140) or caffeine consumption (β = −0.01, p  = 0.948). No group differences in pretreatment symptom scores or caffeine consumption were detected ( p values > 0.86). Conclusion: Habitual caffeine consumption moderated the antidepressant effect of dorsomedial iTBS, consistent with caffeine improving antidepressant pharmacological treatments in animals. Caffeine is an antagonist of adenosine receptors and may enhance antidepressant effects through downstream dopaminergic targets.